Effect of Gd2O3 on radiation shielding, physical and optical properties of sodium borosilicate glass system. (October 2022) - Intachai, N.; Wantana, N.; Kaewjaeng, S.; Chaiphaksa, W.; Cheewasukhanont, W.; Htun, K.T.; Kothan, S.; Kim, H.J.; Kaewkhao, J.
Abstract: The radiation shielding, physical and optical properties were studied with the glass formula in the composition of xGd2 O3 : 40Na2 O: 5SiO2 : (55-x)B2 O3, where x = 0, 2.5, 5, 7.5, 10, 12.5, 15 mol%, respectively. The gadolinium sodium borosilicate glasses were melted entirely by melt quenching technique at 1200 o c. Gamma-ray shielding property was studied with Compton scattering technique from 0.224 MeV to 0.662 MeV gamma-ray energy range. The density and molar volume of the glass samples were increased with higher Gd2 O3 concentration. The glass samples show high transparency which can be observed from transmission spectra. The radiation shielding properties are better with increased Gd2 O3 concentrations. The results of total mass attenuation coefficient, the effective atomic number and the effective electron density showed the theoretical and experimental values are in good agreement and showed similar trends. The best shielding radiation properties were obtained at 15% of Gd2 O3 concentration. At 15% of Gd2 O3 concentration shows the same attenuation behavior with 0.64 mm of lead. The half value layer (0.662 MeV) at 15% of Gd2 O3 concentration is better than the commercial window, serpentine and ordinary concrete. Highlights: Gd2 O3 show highly effective for the radiation shielding material. Radiation shielding properties investigated by using 137 Cs. WinXcom was used to compare the experimental values of shielding properties. The HVL was inquired at 0.662 MeV gamma-ray energy. The lead equivalent thickness obtained by 15 mol% of Gd2 O3 concentration.